Analysis of expressive speech acts in the lyrics of the song titled 'White Space' by Jeong Dong-Won - Samsudin, Didin; Nafisatunnuha, Hasna’; Qur aini, Aziza Nurul Hudayah (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
One form of indirect communication that can be studied pragmatically is communication between writers or authors and readers through works that have been written in accommodating their thoughts and feelings. Sentences that contain the expressions of the author's psychological state and their feelings can be categorized as expressive speech acts which can be analyzed by examining the contexts spoken or written. Song lyrics are also among the works that can be studied pragmatically. This study aims to analyze the lyrics of the song titled "White Space" sung by Jeong Dong-won and written by Kim Jong-hwan to find out the expressive speech acts contained in it. This research was qualitative research using a descriptive qualitative research method because the data obtained were the words and sentences contained in the lyrics as primary data. The results of this study showed that in the song lyrics titled "White Space", the author wrote it (those expressions) implicitly or indirectly. There were various expressions such as sadness (4), regret (2), anxiety (1), pride (1), blame (1),  advice (1), and hope (1). Those were contained in sentences that represent the thoughts and feelings of the author.